Adoption of Bio-security Measures against Avian-Influenza Outbreaks among Poultry Farmers in Jigawa State, Nigeria - Felix Oladipo; Oladele Gafaru Bello; Abdulrazaq Kamal Daudu; Ajoke Oluwatoyin Kayode; Oyedola Waheed Kareem; Oluwasogo David Olorunfemi; Abigail Oluwatunmise Iyilade (Journal of Agricultural Extension, 2020)
Abstract